The Influence of Profitability, Leverage, and Board Characteristics on Corporate Environmental Disclosure in Asia Pacific Market - Maharani, Solehah Ayu; Fuad, Fuad (Department of Accounting, Faculty of Economics & Business, Universitas Diponegoro, 2021)
This Paper Examines the influence of profitability, leverage, and board characteristics on the environmental disclosure under ISO 26000. Data were collected from 5440 firm-year observations from 12 countries in Asia Pacific. Our study finds that profitability, leverage, and board characteristics do not significantly affect environmental disclosure. Nevertheless, this research can explain that the awareness of environmental policy for employees and society must be improved. Especially in maintaining the social and environmental welfare to their surroundings and increasing the demand of the stakeholders.